Relationship between profitability indicators and maximization market value added and intrinsic for the industrial companies - Ali H.Hindi Al-Ali; Sarah K. Ibrahim Al-Shabeeb (Global Business & Finance Review (GBFR), 2024)
Purpose: This research aims to study the impact of profitability indicators on maximizing the market value added and intrinsic value for industrial companies listed on the Iraq Stock Exchange. Design/methodology/approach: The research was structured using the analysis study method, incorporating various financial indicators, such as Net Profit Margin, Basic Earning Power, Return on Assets, Return on Equity, to examine their impact on market value added and intrinsic value. Findings: The researchers utilized financial data form fourteen industrial companies operating in Iraq ; listed in the financial market, spanning the period from 2011 to 2022. The data underwent analysis employing financial methods and various statistical tools, including single and multiple regression analysis as well as transaction analysis. The results revealed that the profitability indicators adopted by the studied companies exerted varied effects on maximizing the market value or intrinsic value. This variance was observed in accordance with the nature and orientations of each company. The underlying reason for this variation can be attributed to the direct relationship of the financial indicators used directly with the investors, thereby influencing management decisions. Research limitations/implications: The paper focuses on four variables representatives of firm profitability indicators to maximize both the market value added and the intrinsic value; it is necessary expanding the independent variables. Originality/value: This research contributes to the literature on Maximizing value levels for industrial companies. It aids firm leaders and decision-makers understanding the significant role of profitability indicators in maximizing value in financial markets by offering a more comprehensive view of their effectiveness.
Keywords: 650; Profitability indicators; Market value added; Intrinsic value; Industrial companies